2004
DOI: 10.1081/imm-120030733
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of B Cell Receptor Signaling on Antigen Endocytosis and Processing

Abstract: B cell receptor (BCR)-mediated antigen processing and presentation involves both the BCR-mediated internalization and processing of cognate antigen as well as the formation and expression of antigenic peptide-MHC class II complexes. While BCR signaling is known to result in changes in the biosynthesis and intracellular trafficking of class II molecules, the effect of BCR signaling on the cell biology of antigen endocytosis and processing is less clear. Therefore, the effect of BCR signaling on the cell biology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Finally, prestimulation of nontransgenic B cells with goat anti-F(abЈ) 2 Ab could not rescue the loss of B cells, thus confirming our earlier results with the C4H3 mAb in resting B cells (Fig. 2, A and B) and our data on the inability of BCR signaling to alter fluid phase uptake and processing of HEL (16).…”
Section: Differential Effect Of Ligation Of Type I and Ii Complexes Fsupporting
confidence: 81%
See 3 more Smart Citations
“…Finally, prestimulation of nontransgenic B cells with goat anti-F(abЈ) 2 Ab could not rescue the loss of B cells, thus confirming our earlier results with the C4H3 mAb in resting B cells (Fig. 2, A and B) and our data on the inability of BCR signaling to alter fluid phase uptake and processing of HEL (16).…”
Section: Differential Effect Of Ligation Of Type I and Ii Complexes Fsupporting
confidence: 81%
“…2B), suggesting that the depletion resulting from ligation of type II complexes is dominant over the lack of depletion observed following ligation of type I complexes. Thus, not only does BCR signaling fail to alter processing of fluid phase Ag (16), but also our data suggest that the signaling function of the type II complex that leads to B cell loss is similarly not significantly affected.…”
Section: Differential Effect Of Ab Ligation Of Type I and Ii Complexementioning
confidence: 67%
See 2 more Smart Citations
“…In addition to facilitating Ag internalization, BCR-induced kinase cascades may be involved in intracellular targeting of BCR-Ag complexes to mature MHC-II loading compartments (17). However, some studies suggest that many of the fundamental endocytic processes required for Ag presentation can occur via phosphorylation-independent BCR endocytosis mechanisms (18,19). We have previously found that cytoskeletal rearrangement processes within dendritic cells are critical for efficient formation of immune synapses with T cells (20); however, it is unknown whether BCR-induced cytoskeletal rearrangements may affect the ability of Ag-bearing B cells to form functional synapses with T cells.…”
mentioning
confidence: 99%